Two-body B meson decays to eta and eta('): observation of B --> eta K*. - Richichi, S; Severini, H; Skubic, P; Undrus, A; Chen, S; Fast, J; Hinson, J; Lee, J; Menon, N; Miller, D; Shibata, E; Shipsey, I; et al. (2000)
In a sample of 19 x 10(6) produced B mesons, we have observed the decays B-->eta K(*) and improved our previous measurements of B-->eta'K. The branching fractions we measure for these decay modes are B(B+-->eta K(*+)) = (26.4(+9.6)(-8.2)+/-3.3)x10(-6), B(B(0)-->eta K(*0)) = (13.8(+5.5)(-4.6)+/-1.6)x10(-6), B(B(+)-->eta'K(+) = (80(+10)(-9)+/-7)x10(-6), and B(B(0)-->eta'K0) = (89(+18)(-16)+/-9)x10(-6). We have searched with comparable sensitivity for related decays and report upper limits for these branching fractions.